Faculty Perceptions of Certifications in Health Education and Public Health: Implications for Professional Preparation. (March 2022) - Blavos, Alexis; Kerr, Dianne; Hancher-Rauch, Heidi; Brookins-Fisher, Jodi; Thompson, Amy
Leaders in the fields of public health and health education/health promotion have been advocating for required credentialing for almost two decades. Recently, some have questioned whether increasing the number of certified professionals could help better differentiate properly trained health educators and public health professionals from others seeking to fill jobs in this professional area. The purpose of this article is to determine how the CHES/MCHES (Certified Health Education Specialist/Master Certified Health Education Specialist) and CPH (Certified in Public Health) credentials are regarded and promoted within the field of health education/health promotion. A cross-sectional survey research design was employed to determine program directors' ( N = 90) views of credentialing issues. The health belief model and the transtheoretical model were used to determine perceived barriers, benefits, and self-efficacy with regard to promoting credentialing and readiness to require the CHES or CPH exam as part of the undergraduate curriculum. Ninety undergraduate programs completed the survey with the majority reporting that they do not require credentialing of faculty and students as part of their program of study. More than 70% of respondents, however, indicated that they thought credentialing in the fields of public health and health education/health promotion is an important issue. Most program directors indicated there is value in having students credentialed in health education or public health, yet few programs required the CHES or CPH exam as part of their curriculum or exit assessment. There are opportunities to use credentialing both in assessing program curriculum alignment with competencies and student mastery of said competencies.